Dispersion properties of GaS studied by THz-TDS - Molloy, John F.; Naftaly, Mira; Andreev, Yury M. 1946-; Lanskii, Grigory V.; Lapin, Ivan N.; Potekaev, Aleksandr I. 1951-; Kokh, Konstantin A.; Shabalina, Anastasiia V.; Shaiduko, Anna V.; Svetlichnyi, Valerii A. (CrystEngComm)
High optical quality centimeter sized GaS crystals are grown using a modified vertical Bridgman method with heat field rotation of the growth melt. Ordinary and extraordinary wave refractive index dispersions are studied by THz time-domain spectroscopy (THz-TDS). New dispersion equations are designed to be suitable for estimating dispersion properties of solid solution GaSe1−xSx crystals from the near IR through the mid-IR and further into the THz range.